2005
DOI: 10.1021/ja0547174
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field and Temperature Dependencies Shed Light on the Recombination Kinetics of a Transition Metal Donor/Acceptor System

Abstract: Abstract:The radical pair recombination of an intramolecular electron-transfer system containing a transition metal moiety has been addressed by femtosecond spectroscopy. The radical pair is formed by ultrafast electron transfer (90 fs) from a ferrocene residue to a photoexcited Nile blue moiety. Its recombination proceeds on the picosecond time scale in a multiexponential fashion. The kinetic pattern is a manifestation of spin processes competing with electron transfer. Magnetic field effects on these kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In the case of semiconductor, where the 2TM model (electron and lattice temperatures) has been effectively applied, the modification of G el by pump fluence has been reported 35 37 . The field-dependent lattice–spin and electron–spin interaction have recently been reported for molecules composed of transition metals 38 , 39 . The modified G ls should modify the temperatures of the spin and lattice.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of semiconductor, where the 2TM model (electron and lattice temperatures) has been effectively applied, the modification of G el by pump fluence has been reported 35 37 . The field-dependent lattice–spin and electron–spin interaction have recently been reported for molecules composed of transition metals 38 , 39 . The modified G ls should modify the temperatures of the spin and lattice.…”
Section: Resultsmentioning
confidence: 99%
“…[17] In chemical reactions, the formation of various reactive oxygen species (ROS), such as singlet oxygen, hydroxyl radicals, and superoxide radicals, influences catalytic activity. Gilch et al [18] studied the electron transfer kinetics involved in free radical reactions using femtosecond spectroscopy, and found that magnetic fields can effectively influence electron transfer between free radicals. Therefore, the effect of magnetic fields on the rate of free radical generation is an important factor.…”
Section: Radical Pair Theorymentioning
confidence: 99%
“…[1][2][3][4][5][6] Among reported routes, the employment of a magnetic field has been considered as an effective strategy, and significant advances have been achieved in different catalysis fields, including photocatalysis, [7][8][9][10][11] electrocatalysis, [11][12][13][14][15][16][17] and thermocatalysis, [18] leading to significantly enhanced performance and allowing for wireless control of catalytic reactions. [19,20] It is concluded that magnetic fields can affect the spin polarization of magnetic materials, thereby accelerating the movement of free charge carriers and increasing the rate of electron transfer to the surface and generation of free radicals participating in catalytic reactions. [1,7,21] As well as being an invaluable variable, the magnetic field can be used as an effective controller of both the product and the rate of a chemical reaction process.…”
mentioning
confidence: 99%